1995
DOI: 10.1007/bf00422375
|View full text |Cite
|
Sign up to set email alerts
|

Glucose intolerance and impairment of insulin secretion in relation to vitamin D deficiency in East London Asians

Abstract: Vitamin D deficiency reduces insulin secretion and still occurs in East London Asians in whom the prevalence of diabetes mellitus is at least four times that of Caucasians. Vitamin D status was assessed in 44 of 65 non-diabetic subjects 'at risk' of diabetes (spot blood glucose level >6.0 mmol/l <2 h post cibum, or>4.6 mmol/l >2 h post cibum on two separate occasions) and in 15 of 60 age and sex-matched 'low-risk' control subjects who attended for oral glucose tolerance test (OGTT) after screening of 877 omniv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
212
4
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 331 publications
(233 citation statements)
references
References 28 publications
12
212
4
2
Order By: Relevance
“…Studies showing an inverse association of serum concentration of 25(OH)D with insulin resistance (IR) and b-cell dysfunction provided a further possible explanation for the inverse association between serum concentrations of vitamin D and the prevalence of the MetS (10)(11)(12)(13). Impaired glucose-mediated insulin production and/or IR are key components of the MetS.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showing an inverse association of serum concentration of 25(OH)D with insulin resistance (IR) and b-cell dysfunction provided a further possible explanation for the inverse association between serum concentrations of vitamin D and the prevalence of the MetS (10)(11)(12)(13). Impaired glucose-mediated insulin production and/or IR are key components of the MetS.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D repletion improves insulin sensitivity and insulin secretion in animal studies (25). Hypovitaminosis D has been proposed as a risk factor for reduced insulin secretion, impaired glucose tolerance, and type 2 diabetes in adults (23)(24)(25)(26)(27)(28)(29). However, some studies in obese adults demonstrated no relationship between vitamin D, PTH, and insulin sensitivity (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the NOD mouse (an excellent animal model of IDDM) vitamin D3 administration prevents the development of IDDM as well as the associated autoimmune insulitis [25]. In a recent study in Bangladeshi subjects living in east London, vitamin D levels were found to be reduced in those most at risk for non-insulin-dependent diabetes [26]. Therefore, we have studied the vitamin D receptor (VDR) locus on chromosome 12q as a candidate gene for IDDM susceptibility in Southern Indian subjects using the transmission disequilibrium test (TDT) [27,28] in family trios consisting of parents and affected offspring.…”
mentioning
confidence: 99%